Sensible temperature at the Łeba Sandbar (Słowiński National Park) on selected days of the 2010 summer season - Półrolniczak, Marek (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2011)
The analysis was performed on the basis of weather measurements conducted in the Słowiński National Park at the Łeba Sandbar in the period from 8th July to 6th August 2010. Two biometeorological indices were calculated: the effective temperature (ET) and the radiative-effective temperature (RET). The daily course of RET was used to select the typical days, which were then subjected to a detailed analysis. This consisted in assessing the influence of individual meteorological elements and the synoptic situation on the development of the values of the RET and ET indices. A considerable diversity of sensible conditions was determined, as well as the considerable variability thereof during the day, in particular during the movement of atmospheric fronts. The sensible conditions were also influenced by factors connected with local circulation and the presence of the sea. Finally, a considerable decrease in the values of RET and ET was observed during changes in wind direction, namely when the wind was blowing from the northern sector.
Keywords: radiative-effective temperature; effective temperature; Łeba Sandbar